Post-COVID 19 Period: Modern State and Clinical Features - V. N. Larina; A. A. Ryzhikh; L. I. Bikbaeva (SINAPS LLC, 2021)
Coronavirus disease (COVID-19) has proven to be a major global public health crisis, as evidenced by the steady increase in re-infected patients. In spite of the fight against this infection going on for more than a year, the unpredictable consequences of COVID-19, with or without concomitant chronic diseases, are still insufficiently studied, which undoubtedly is an additional burden on the outpatient health care unit. This article is a review of the available modern literature on the features of the course and duration of the post-COVID period. More than fifteen studies have been analyzed, in which the authors evaluated the incidence of symptoms in post-COVID period and its clinical characteristics.